2015
DOI: 10.1007/s00426-015-0649-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning under your gaze: the mediating role of affective arousal between perceived direct gaze and memory performance

Abstract: Previous studies have shown that cognitive performance can be affected by the presence of an observer and self-directed gaze. We investigated whether the effect of gaze direction (direct vs. downcast) on verbal memory is mediated by autonomic arousal. Male participants responded with enhanced affective arousal to both male and female storytellers' direct gaze which, according to a path analysis, was negatively associated with the performance. On the other hand, parallel to this arousal-mediated effect, males' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 73 publications
0
19
1
Order By: Relevance
“…In fact, direct gaze from a real person leads to changes in skin conductance response compared to conditions without direct gaze (Myllyneva and Hietanen 2015a). Changes in arousal from direct gaze may also account for performance in a memory task (Helminen et al 2015). These studies support Zajonc’s claim that being in the presence of another person leads to change in arousal, but do not rule out a parallel role for mentalising processes.…”
Section: The Audience Effect In Typical Populationsmentioning
confidence: 99%
“…In fact, direct gaze from a real person leads to changes in skin conductance response compared to conditions without direct gaze (Myllyneva and Hietanen 2015a). Changes in arousal from direct gaze may also account for performance in a memory task (Helminen et al 2015). These studies support Zajonc’s claim that being in the presence of another person leads to change in arousal, but do not rule out a parallel role for mentalising processes.…”
Section: The Audience Effect In Typical Populationsmentioning
confidence: 99%
“…Some of these studies report that memory for an image of face (Hood et al., 2003; Mason et al., 2004; Smith et al., 2006) and for words (Fry and Smith, 1975; Kelley and Gorham, 1988; Macrae et al., 2002; Falck-Ytter et al., 2014) is improved when these stimuli are associated with direct gaze (though see Beattie, 1981; Conty et al., 2010; Nemeth et al., 2013). In the investigations that have used live people as stimuli, a speaker’s eye contact has been associated with improved memory for what the speaker has said (Otteson and Otteson, 1980; Sherwood, 1987; Fullwood and Doherty-Sneddon, 2006; Helminen et al., 2016). Some of the earliest studies examined how children’s academic performance could be affected by a teacher’s eye contact (Otteson and Otteson, 1980; Sherwood, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sherwood (1987) suggested that learning could be enhanced in a classroom when instructors made eye contact with members in the audience. In a more recent study, male participants remembered more details from a story told by a male storyteller who looked at them relative to a storyteller who looked away, but female participants did not (Helminen et al., 2016). The research using images and live people as stimuli seems to indicate that eye contact enhances the processing and retention of information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the gaze provides more information than the brain can process and thus, relies on ‘selective visual attention’ to cope [26]. As a result, individuals are looking for gaze signals from the eye region to understand a person’s focus of attention, mental state, and intentions [82]. Thus, the findings of two positive and significant relationships between prototype of sensitivity, and (a) the nasion, and (b) the upper nose regions are not surprising.…”
Section: Discussionmentioning
confidence: 99%